Effect of ragi tape fermentation on physicochemical properties, phenolic compounds, and antioxidant capacity of turmeric spent - Dewi Cakrawati; Yatti Sugiarti; Sri Handayani (AGROINTEK, 2024)
Turmeric spent availability is high due to the increasing production of turmeric herb drinks. However, turmeric spent utilization is low, although it still contains phenolic compounds and antioxidant capacity. This study aims to investigate the effect of fermentation on the physicochemical characteristics of turmeric spent. Ragi tape is used as a starter since it contains various microorganisms. The community of microorganisms in the ragi could inhibit the growth of unwanted microorganisms, thus preventing contamination. Physicochemical characteristics, namely water-holding capacity, swelling capacity, oil-holding capacity, glucose content, crude fiber content, total phenol content, and antioxidant capacity, were observed from non-fermented and fermented turmeric spent. The results show that the duration of fermentation does not affect the physicochemical properties, total phenolic content, antioxidant capacity, and reducing sugars content. Ragi tape contains low concentrations of A. oryzae. Moreover, ragi tape is a consortium of microorganisms consisting of fungi, yeast, and lactic acid bacteria, so further study is needed to investigate the interaction between microorganisms and metabolite production